Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy with or without early post-operative intraperitoneal chemotherapy for appendix neoplasms with peritoneal metastases: A propensity score analysis. Issue 1 (January 2021) - Soucisse, Mikael L.; Fisher, Oliver; Liauw, Winston; Ghanipour, Lana; Cashin, Peter
Abstract: Introduction: – Early post-operative intraperitoneal chemotherapy (EPIC) can be used after cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) in patients with resectable peritoneal metastases (PM). Whether EPIC adds any benefit is debatable. Methods: – We performed a retrospective case-control analysis of patients with PM of appendiceal origin treated by CRS + HIPEC ± EPIC at Uppsala University Hospital between 2004 and 2012. The 206 patients were divided into two groups depending on if they received EPIC or not. The two groups were propensity-matched with a 1:1 ratio. The patients in the EPIC group were mostly operated in the first three years of the unit's experience. Results: – After matching, 76 patients were left in each group. The groups were similar, except for the proportion of histological subtypes (p = 0.021) and chemotherapy agents used for HIPEC (0.017). Survival outcomes were stratified by histology. The patients who received EPIC had a longer hospital and ICU length of stay (15.71 vs 14.28 days, p = 0.049), (1.45 vs 1.05 days, p = 0.002), respectively. Post-operative complications were similar in both groups. Overall Survival (OS) and recurrence-free survival (RFS) did not differ for the patients with low-grade histology. The patients with high-grade tumors who received EPIC had a significantly worse OS (p = 0.0088) while having the same RFS as the patients who did not receive EPIC. Conclusion: Our results suggest there is no benefit of EPIC in patients with advanced appendiceal tumors while increasing hospital and ICU length of stays. A suboptimal group matching might influence our results. Highlights: Early post-operative intraperitoneal chemotherapy (EPIC) does not appear to be associated with increased morbidity. EPIC does not seem to be beneficial in terms of recurrence-free and overall survival EPIC is associated with longer intensive care unit and hospital stay